2020
DOI: 10.1186/s12876-020-01467-w
|View full text |Cite
|
Sign up to set email alerts
|

Carbon tetrachloride (CCl4) accelerated development of non-alcoholic fatty liver disease (NAFLD)/steatohepatitis (NASH) in MS-NASH mice fed western diet supplemented with fructose (WDF)

Abstract: Background Multiple murine models of nonalcoholic fatty liver disease/steatohepatitis (NAFLD/NASH) have been established by using obesogenic diets and/or chemical induction. MS-NASH mouse (formally FATZO) is a spontaneously developed dysmetabolic strain that can progress from hepatosteatosis to moderate fibrosis when fed a western diet supplemented with 5% fructose (WDF). This study aimed to use carbon tetrachloride (CCl4) to accelerate and aggravate progression of NAFLD/NASH in MS-NASH mouse. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…Furthermore, NAFLD can be induced by feeding mice different kinds of diets, including a high-fat diet (HFD) [19], high-carbohydrate diet (HCD) [20], methionine-and choline-deficient (MCD) diet [21], and fast food (FF) diet [22]. Furthermore, to reach the NASH and fibrosis stage, some models need to be triggered by a second stimulus or agent ("second hit"), such as tunicamycin [23], dexamethasone [24], and carbon tetrachloride (CCl 4 ) [25]. It was found that male C57BL/6J mice fed a high-fat, -sucrose, and -cholesterol diet with high fructose or glucose water and injected with CCl 4 showed the closest similarity to the human NAFLD pattern [26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NAFLD can be induced by feeding mice different kinds of diets, including a high-fat diet (HFD) [19], high-carbohydrate diet (HCD) [20], methionine-and choline-deficient (MCD) diet [21], and fast food (FF) diet [22]. Furthermore, to reach the NASH and fibrosis stage, some models need to be triggered by a second stimulus or agent ("second hit"), such as tunicamycin [23], dexamethasone [24], and carbon tetrachloride (CCl 4 ) [25]. It was found that male C57BL/6J mice fed a high-fat, -sucrose, and -cholesterol diet with high fructose or glucose water and injected with CCl 4 showed the closest similarity to the human NAFLD pattern [26].…”
Section: Introductionmentioning
confidence: 99%
“…Even the rise in ALT and AST levels noted here in MS-NASH mice (reaching 300-500 U/mL), while substantial, are not necessarily evidence of serious liver damage. Acute chemical-induced liver toxicity in mice is associated with ALT / AST levels in the range of 3000-6000 U/mL (12).…”
Section: Discussionmentioning
confidence: 99%
“…Even after 25 weeks, however, these changes are generally mild. Some studies have reported widespread liver damage (beyond steatosis) at earlier time-points but, typically, liver toxins such as carbon tetrachloride, thioacetamide or alcohol are administered along with the high-fat diet (12,13). Animals with severe genetic anomalies (14) or animals maintained on a toxic, nutrient-restricted diet such as the methionine-and choline-deficient diet (15) may develop severe liver anomalies more rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention was performed for six weeks to induce hepatic steatosis. In this regard, Zhang et al (2020) examined the effect of CCl 4 injection on NAFLD induction; the CCl 4 dose in the present study was based on the results of their study. Besides, because we did not achieve definite results in the groups during the pilot study, we modified the prescribed dose of CCl 4 to an intermediate level (0.1 mL/kg) between the two doses used by Zhang et al (0.2 and 0.08 mL/kg) (9).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…When combined with a Western diet rich in fat and fructose, it can induce oxidative stress, inflammation, and apoptosis. As fibrosis progresses in hepatocytes, fatty liver leads to steatosis; CCl 4 induces NAFLD through this mechanism (7)(8)(9). In previous studies, steatosis and hepatic fibrosis were induced via CCl4 injection at doses of 0.2 mL/kg (8, 10), 0.5 -0.7 mL/kg (11,12), 1 mL/kg (13), and 2 mL/kg (14).…”
Section: Introductionmentioning
confidence: 99%